Anodic zno microsheet coating on zn with sub-surface microtrenched zn layer reduces risk of localized corrosion and improves bioactivity of pure zn - Dong, Hongzhou; Virtanen, Sannakaisa (Coatings, 2021)
Zinc-based alloys are emerging as an alternative to magnesium-and iron-based alloys for biodegradable implant applications, due to their appropriate corrosion performance and biocompatibility. However, localized corrosion occurring on the zinc surface, which is generally associated with restricted mass transport at specific surface sites, such as in confined crevices, declines mechanical strength and can lead to the failure of implant materials. In order to improve corrosion behavior and bioactivity, we explore the effect of a ZnO microsheet coating fabricated on pure Zn via anodic oxidization. Samples were characterized with Scanning Electron Microscope (SEM) (including Energy Dispersive Spectroscopy (EDS), X-ray Photoelectron spectroscopy (XPS), Fourier Transform Infrared Spectroscopy (FTIR), and X-ray Diffraction (XRD)). The microstructured surface consists of parallel Zn trenches on the bottom and ZnO/Zn3 O(SO4 )2 sheets on the top. This layer shows favorable Ca-phosphate precipitation as well as bovine serum albumin (BSA) adsorption properties. Electrochemical experiments indicate an increased corrosion resistance of surface-modified Zn by the presence of BSA in simulated body fluid. Most noteworthily, localized corrosion that has been previously observed for pure Zn in BSA-containing electrolytes does not occur on the Zn/ZnO-coated surface.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Albumin; Biodegradable metals; Corrosion behavior; Zn; ZnO